Factors influencing glycaemic control behaviours among individuals with type 2 diabetes mellitus at Royal Prima Hospital, Medan - Rafika, Nazla Ghina; Hulu, Victor Trismanjaya; Sihotang, Widya Yanti (Buletin Kedokteran & Kesehatan Prima, 2025)
Elevated blood glucose levels are indicative of a chronic metabolic disorder known as type 2 diabetes mellitus (T2DM), which necessitates long-term management through effective glycaemic control. Poor glycaemic control behaviours can elevate the risk of severe complications, diminish quality of life, and increase economic burden. This study aimed to analyse the determinants of glycaemic control behaviours in individuals with T2DM at Royal Prima Hospital Medan. A quantitative design employing a cross-sectional method was utilised. The study population comprised all patients with T2DM registered at Royal Prima Hospital Medan. A sample of 182 participants was recruited using consecutive sampling. Data were collected via questionnaires and secondary data from patient medical records. Data analysis included univariate analysis, chi-square tests, and logistic regression for bivariate analysis. The findings of this study demonstrated a significant association between medication adherence and glycaemic control behaviours in individuals with T2DM.